Disability in the Hebrew Bible: interpreting mental and physical differences - Olyan, Saul M. (Cambridge University Press, 2008)
Mental and physical disability, ubiquitous in texts of the Hebrew Bible, here receive a thorough treatment. Olyan seeks to reconstruct the Hebrew Bible's particular ideas of what is disabling and their potential social ramifications. Biblical representations of disability and biblical classification schemas - both explicit and implicit - are compared to those of the Hebrew Bible's larger ancient West Asian cultural context, and to those of the later Jewish biblical interpreters who produced the Dead Sea Scrolls. This study will help the reader gain a deeper and more subtle understanding of the ways in which biblical writers constructed hierarchically significant difference and privileged certain groups (e.g. persons with 'whole' bodies) over others (e.g. persons with physical 'defects'). It also explores how ancient interpreters of the Hebrew Bible such as the Qumran sectarians reproduced and reconfigured earlier biblical notions of disability and earlier classification models for their own contexts and ends.